Effects of the Southward extension on the EC—Labour market - Elmar Hönekopp; Heinz Werner (Intereconomics, 1979)
The European Community will be enlarged in the next few years by the accession of Greece, Portugal and Spain. Which will be the consequences for the labour market of the EC and the Federal Republic of Germany in particular?
Keywords: 330; Intregration